Muslim Students’ Perceptions on English Medium Instruction for Mathematics and Natural Science Subjects - Kurniawati, Atin; Atmojo, Arief Eko Priyo (Institut Agama Islam Negeri Kudus, 2025)
This study sheds some light on the implementation of English medium instruction (EMI) for mathematics and natural science subjects at an Islamic secondary school in Surakarta, Indonesia, how the Muslim students perceive its implementation, and their attitudes towards EMI. A qualitative method was adopted in this study. Seven Muslim students were purposively chosen as the participants. Data were garnered through written reflections and focus group discussions. Two significant others were also employed. Thematic coding was used to analyze the data. The findings indicated that EMI was implemented by providing learning materials, media, learning activities, and classroom instructions in English. The school also provided preparation programs and supporting programs to optimize EMI. Although many Muslim students found difficulties due to the lack of English proficiency in the early stage, they perceived the implementation of EMI positively since it facilitated them to understand the learning materials of content knowledge and developed their English proficiency. Furthermore, EMI also developed their learning motivation and encouraged them to find learning strategies that suited them best. Pedagogical and curricular implications were also discussed. Ultimately, future studies on EMI are encouraged and directed with key points.